Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Transforming an elliptic PDE into the Laplace equation?

  1. Apr 29, 2008 #1
    For an elliptic PDE Uxx + Uyy + Ux + Uy = -1 in D = {x^2 + y^2 = 1} and U = 0 on the boundary of D = {x^2 + y^2 = 1}
    is it possible for me to make a change of variables and eliminate the Ux and Uy and get the Laplace equation Uaa + Ubb = 0?

    I tried converting into polar coordinates, but the Ux and Uy don't seem to cancel out. Or am I approaching this the wrong way?
     
  2. jcsd
  3. Apr 30, 2008 #2

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    You can't get rid of the "Ux" and "Uy" by changing the independent variables but you can by letting V(x,y)= e-(1/2)(x+ y)U(x,y).
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?



Similar Discussions: Transforming an elliptic PDE into the Laplace equation?
Loading...